Chagas disease (Trypanosoma cruzi) and HIV co-infection in Colombia (2014)
Chagas disease is a complex zoonotic pathology caused by the kinetoplastid Trypanosoma cruzi. This parasite presents remarkable genetic variability and has been grouped into six discrete typing units (DTUs). The association between the DTUs and clinical outcome remains unknown. Chagas disease and co-infection with HIV/AIDS has been reported widely in Brazil and Argentina. Herein, we present the molecular analyses from a Chagas disease patient with HIV/AIDS co-infection in Colombia who presented severe cardiomyopathy, pleural effusion, and central nervous system involvement. A mixed infection by T. cruzi genotypes was detected. We suggest including T. cruzi in the list of opportunistic pathogens for the management of HIV patients in Colombia. The epidemiological implications of this finding are discussed. © 2014 The Authors.